Ginsenoside Rg1 Prevents Cognitive Impairment and Hippocampal Neuronal Apoptosis in Experimental Vascular Dementia Mice by Promoting GPR30 Expression. (3rd December 2021) - Shen, Fengming; Wang, Juan; Gao, Feng; Wang, Jingji; Zhu, Guoqi
Abstract : This study is aimed at investigating the potential roles of G protein-coupled estrogen receptor 1 (GPER, also known as GPR30) in the preventive effect of ginsenoside Rg1 against cognitive impairment and hippocampal cell apoptosis in experimental vascular dementia (VD) in mice. The effects of bilateral common carotid artery stenosis (BCAS) on GPR30 expression at mRNA level were evaluated. Thereafter, the BCAS mouse model was utilized to evaluate the protection of Rg1 (0.1, 1, 10 mg/kg, 14 days, ip ). Spatial memory was evaluated by water Morris Maze 7 days post BCAS. After behavioral tests, neuronal apoptosis was detected by terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling assay, and potential mechanisms were determined using western blotting and quantitative real-time PCR. Our results showed that GPR30 expression in the hippocampal region at mRNA level was promoted 30 min, 3 h, 6 h, and 24 h following BCAS. Ginsenoside Rg1 (1 or 10 mg/kg, 14 days, ip ) promoted GPR30 expression in the hippocampus of model mice (after behavioral tests) but did not alter GPR30 expression in the hippocampus of control mice. Moreover, treatment of ginsenoside Rg1 (10 mg/kg) or G1 (5  μ g/kg), a GPR30 agonist, prevented BCAS-induced memory impairment and hippocampal neuronal loss and apoptosis and promoted the ratio of Bcl-2 to Bax expression in the hippocampus (after behavioral tests). On the contrary, G15 (185  μ g/kg), an antagonist of GPR30, aggravated BCAS-induced hippocampal neuronal loss and apoptosis. Finally, drug-target molecular docking pointed that Rg1 had a lower binding energy with GPR30 compared with Bax and Bcl-2. Together, our data implicate that ginsenoside Rg1 prevents cognitive impairment and hippocampal neuronal apoptosis in VD mice, likely through promoting GPR30 expression. These results would provide important implications for the application of Rg1 in the treatment of VD.